(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The Organization of American States (OAS) is an international organization build to promote solidarity and political cooperation among American States. In order to achieve its purposes, it provides a procedure of suspension/expulsion of a member State in case of violation of human rights and fundamental liberties. The chronicle analyzes the procedure and deals with specific cases of Cuba and Honduras.